MOSCOW EDUCATIONAL SERVICE AND LABOUR MARKETS FOR YOUNG SPECIALIST UNDER INNOVATIVE ECONOMY CONDITIONS - A. Nikolaeva; A. Vasilieva (Вестник университета, 2017)
One of the biggest issues that the society is facing currently is employment for young specialists. The major conclusion here suggests that given the current socio-economic factors graduates’ competitive capacity depends on the degree to which their knowledge and skills match the expectations posed both by the profession itself and by the employer. Recommendations on the organization of interaction between key stakeholders of labor markets and education were offered.